Efficacy and Safety of Nicotinamide 10%, Associated with Magnesium Ascorbyl Phosphate 5% and Hyaluronic Acid 5%, Compared to Hydroquinone 4% in Women with Facial Melasma: A Randomized, Double-Blind, Controlled Clinical Trial. - Barbosa, Mayla [UNESP]; de Amorim, Rebecca Perez [UNESP]; Cassiano, Daniel; Dias, Marina [UNESP]; de Abreu, Ana Flávia [UNESP]; Bagatin, Edileia; Miot, Hélio Amante [UNESP]; Espósito, Ana Cláudia Cavalcante [UNESP] (Taylor & Francis, 2024)
Background: Nicotinamide has demonstrated efficacy in the treatment of melasma. Topical antioxidants and humectants may enhance its performance. Currently, there is no controlled trial on the combination of 10% nicotinamide, 5% magnesium ascorbyl phosphate, and 5% hyaluronic acid, a dermo-cosmetic compound, in comparison to 4% hydroquinone for the treatment of melasma. This study aimed to explore the tolerability and efficacy of the association of the combined product versus hydroquinone. Methods: A randomized, double-blind trial involving women with facial melasma was conducted. Participants were instructed to apply the combined product (NIC group) twice daily or 4% hydroquinone for 60 days (HQ group) at night and placebo in the morning. Evaluations were performed at inclusion, after 14 and 60 days of treatment, measuring the modified Melasma Area and Severity Index (mMASI), Melasma Quality of Life Scale (MELASQoL), and colorimetric luminosity. The Global Aesthetic Improvement Scale (GAIS) was assessed by a blinded evaluator. Results: Both interventions led to a progressive improvement in mMASI, MELASQoL, and GAIS, without a difference between them on D14 and D60 (p>0.2). For NIC, the mean reduction (95% CI) in mMASI was 16% (8–24%) on D14 and 32% (23–41%) on D60, while for HQ, it was 10% (7–24%) on D14 and 43% (34–52%) on D60. Reduction in colorimetric luminosity was greater in the HQ group at D60 (p=0.01). No serious side effects were identified. Of the initially included 50 patients, one was lost to follow-up in the HQ group on D60, and one withdrew consent from the NIC group, both unrelated to treatment. Conclusion: The association of 10% nicotinamide, 5% magnesium ascorbyl phosphate, and 5% hyaluronic acid was safe and well-tolerated, although its overall clinical efficacy was numerically inferior to 4% hydroquinone. This regimen can be considered for patients with poor tolerability to hydroquinone. Clinical Trial Registration: #RBR-4mkfmr8.
Keywords: antioxidants; hydroquinone; hyperpigmentation; melasma; nicotinamide